2018
DOI: 10.1096/fj.201701424r
|View full text |Cite
|
Sign up to set email alerts
|

OC‐STAMP promotes osteoclast fusion for pathogenic bone resorption in periodontitis via up‐regulation of permissive fusogen CD9

Abstract: Cell fusion-mediated formation of multinuclear osteoclasts (OCs) plays a key role in bone resorption. It is reported that 2 unique OC-specific fusogens [ i.e., OC-stimulatory transmembrane protein (OC-STAMP) and dendritic cell-specific transmembrane protein (DC-STAMP)], and permissive fusogen CD9, are involved in OC fusion. In contrast to DC-STAMP-knockout (KO) mice, which show the osteopetrotic phenotype, OC-STAMP-KO mice show no difference in systemic bone mineral density. Nonetheless, according to the ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 56 publications
0
47
0
Order By: Relevance
“…Consequently, emerging trends in the field of personalized medicine in periodontics have led to the study of different molecules based on oral fluids, among which saliva has demonstrated an enormous potential for diagnostic applications, discriminating patient stratification models, as well as prognosis and personalized treatment (Brinkmann, Zhang, Giannobile, & Wong, ; Ebersole, Nagarajan, Akers, & Miller, ; Giannobile, ; Korte & Kinney, ; Nagarajan, Al‐Sabbagh, Dawson, & Ebersole, ; Nagarajan, Miller, Dawson, Al‐Sabbagh, & Ebersole, ). In this line, although some studies have postulated the association of exosome‐related tetraspanins with periodontal disease as detected in gingival crevicular fluid (Bisson‐Boutelliez et al., ) and tissue murine model (Ishii et al., ), nothing is known regarding the salivary levels of these proteins and their relationship with the periodontal health/disease status. To the best knowledge of the authors, this study represents the first reference on salivary quantitation of CD9 and CD81 exosome‐related tetraspanins in a representative sample of individuals with different periodontal status using a full‐mouth examination along ELISA‐based measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, emerging trends in the field of personalized medicine in periodontics have led to the study of different molecules based on oral fluids, among which saliva has demonstrated an enormous potential for diagnostic applications, discriminating patient stratification models, as well as prognosis and personalized treatment (Brinkmann, Zhang, Giannobile, & Wong, ; Ebersole, Nagarajan, Akers, & Miller, ; Giannobile, ; Korte & Kinney, ; Nagarajan, Al‐Sabbagh, Dawson, & Ebersole, ; Nagarajan, Miller, Dawson, Al‐Sabbagh, & Ebersole, ). In this line, although some studies have postulated the association of exosome‐related tetraspanins with periodontal disease as detected in gingival crevicular fluid (Bisson‐Boutelliez et al., ) and tissue murine model (Ishii et al., ), nothing is known regarding the salivary levels of these proteins and their relationship with the periodontal health/disease status. To the best knowledge of the authors, this study represents the first reference on salivary quantitation of CD9 and CD81 exosome‐related tetraspanins in a representative sample of individuals with different periodontal status using a full‐mouth examination along ELISA‐based measurements.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are characterized by their ability to laterally organize membrane proteins by interacting in cis with transmembrane receptors, adhesion molecules, enzymes, signalling proteins and each other, thus forming functional tetraspanin‐enriched microdomains (Hemler, ; Charrin et al., ; Yáñez‐Mó, Barreiro, Gordon‐Alonso, Sala‐Valdés, & Sánchez‐Madrid, ), which are involved in numerous biological processes that imply cell adhesion, motility, invasion and membrane fusion as well as signalling and protein trafficking (Andreu & Yáñez‐Mó, ). Although it has been demonstrated that modulation of the expression and/or activity of some tetraspanins such as CD9 in T lymphocytes, polymorphonuclear neutrophils (PMN) and epithelial cells (EC) may be one of the factors of the immune response that could influence the activity of periodontitis in response to bacterial challenge (Bisson‐Boutelliez, Miller, Demarch, & Bene, ; Ishii et al., ), little is known regarding the salivary levels of this exosome‐related protein and its relationship with the degree of periodontal breakdown. Moreover, although it has been postulated that CD81 tetraspanin acts as complementary costimulator of human T‐cell subpopulations (Sagi, Landrigan, Levy, & Levy, ), its role in the aetiopathogenesis of periodontitis has not been analysed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CD9 made functions by regulating gp130 protein stability to maintain the self-renewal of cell differentiation [33]. CD9 acted as a cell surface protein and had been reported to be a significant fusogenic gene in maintaining the fusion of osteoclasts [34]. CD9 stabilized the IL-6 receptor subunit gp130, which in turn promoted the activation of STAT3 phosphorylation [35].…”
Section: Agingmentioning
confidence: 99%
“…Osteoclast function is regulated by several crucial transcription factors, including nuclear factor of activated T cells c1 (NFATc1) and c-Fos. The NF-κB, MAPK, and immune receptor tyrosine-based activation motif (ITAM) signaling pathways, converge to induce the expression of NFATc1, a key regulator that drives osteoclast differentiation, increasing the expression of osteoclast-related marker genes including dendritic cell-specific transmembrane protein (Dc-STAMP) and cathepsin K (CTSK) [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%